INVESTIGATION INTO THE CAUSES OF PREMATURE CORROSION OF PRE-FABRICATED STEEL FACTORY BUILDING (Journal of Mechanical Engineering, 2010)
Premature corrosion of steel roof panels of a prefabricated factory building was reported just two months’ after installation. In order to find out the causes of this corrosion, physical investigation of the affected roof was carried out and samples of the panels and relevant information were collected. Laboratory tests were carried out on the samples using light optical microscopy, scanning electron microscopy (SEM), energy dispersive X-ray micro analysis (EDX) and tensile tests. Test results show that the steel roof was constructed from painted as well as Al-Zn coated steel sheet, conforming to ASTM A 792M Grade 340 and ASTM A 792M-A150. Analysis of other results suggests that the rusts were superficial in nature and they did not start from the steel sheet of the roof panels. Based on the superficial nature of the rust spots, their morphology, chemical analysis etc., it is believed that rust spots were caused by the corrosion of steel swarfs that deposited on the roof panels. The swarfs originated from drilling, cutting and riveting operations during installation. Proper cleaning of the roof immediately after installation could have avoided the problem. Importance of awareness about the danger of improper cleaning and regular maintenance of roof panels after installation is discussed.Keywords: Premature corrosion; galvanized; steel debris; roof panel; superficial.DOI: 10.3329/jme.v40i2.5349Journal of Mechanical Engineering, Vol. ME 40, No. 2, December 2009 90-94